Analysis of the Effects of Macroprudential Policy Instruments on Commercial Bank Liquidity in Indonesia 2018-2021 Period - Maulidina Nur Budiastuti; Harya Kuncara Wiralaga; Siti Fatimah Zahra (Yayasan Education and Social Center, 2022)
Liquidity is an important aspect that can be considered a bank's lifeblood. To maintain business continuity, banks must always manage liquidity effectively. Liquidity easing is one strategy to assist economic growth during the COVID-19 epidemic—instances where macroprudential policies are employed to relax limits on liquidity. The government's goal, which is to foster increased economic growth, is to increase the amount of money lent to people in debt. On the other hand, this easing of liquidity is thought to help maintain bank operations solvent. This easing of liquidity during the pandemic carries out by reducing the reserve requirement, followed by an increase in the MPLB ratio. In addition, Bank Indonesia strengthened RIM by adding an export money order in its calculation. This research aims to look at how macroprudential policy, such as the Statutory Reserves instrument, the Macroprudential Intermediation Ratio, and the Macroprudential Liquidity Buffer, affects the liquidity of traditional commercial banks in Indonesia from 2018 to 2021. The monthly data comes from the Financial Services Authority website, specifically the Indonesian Banking Statistics section. To evaluate the three hypotheses, the researchers employed a multiple linear regression approach utilizing EViews 10 software. First, the Statutory Reserves have a negative and minor influence on commercial bank liquidity, according to the findings. Second, RIM has a good and considerable impact on commercial bank liquidity. Third, PLM has a considerable negative impact on commercial bank liquidity. Simultaneously, it discovers that three separate elements influence the liquidity of commercial banks